The Development of British Counter-Insurgency Intelligence - Charters, David (Journal of Conflict Studies)

(untitled) (The University of New Brunswick, 2009)
ABSTRACT The centrality of intelligence to counter-insurgency operations and campaigns is now widely acknowledged, but this has not always been the case, even for Great Britain, which is generally regarded as the world leader in counter-insurgency. By examining operational experience, doctrine and training, and professional writing on the subject, this article will show how intelligence emerged as a centerpiece of British counter-insurgency theory and practice in the post-war era. It will demonstrate that the British experienced a steep learning curve. Sound theory and practice were no guarantee of success, since victory or defeat was determined largely by local conditions and British political considerations, and some intelligence practices that had been effective in distant conflicts proved problematic when applied in the domestic arena of Northern Ireland. Ultimately, British counter-insurgency theory and practice became ‘intelligence-driven.’